ANALISIS KEMAMPUAN MENGGAMBAR ORNAMEN SUKU BATAK KARO MOTIF PANTIL MANGGUS PADA MEDIA STYROFOAM SISWA KELAS X SMK NEGERI 1 BERASTAGI - Fitri Risnawati; Surniati Chalid (Universitas Negeri Medan, 2019)
ABSTRACT This study aims to determine the level of drawing ability of Karo Batak Ornaments in the Pantil Manggus Motif on Styrofoam Media for Class X Students of SMK Negeri 1 Berastagi. The study was conducted on November 20, 2017. The population in this study were all students of class X Kria Tekstil, Berastagi State Vocational School consisting of 3 classes totaling 92 students. The results of this study indicate that the ability to draw ornaments of the Batak Karo tribe in the pantil manggus motif on Styrofoam media in class X SMK Negeri 1 Berastagi is good. The average results of calculating the ability of students is 89.5 standard deviations of 3.40 with the highest value of 96 and the lowest value of 83. Keywords: Ornaments, Styrofoam ABSTRAKPenelitian ini bertujuan untuk mengetahui Tingkat Kemampuan Menggambar Ornamen Suku Batak Karo Motif Pantil Manggus Pada Media Styrofoam Siswa Kelas X SMK Negeri 1 Berastagi. Penelitian dilaksanakan pada tanggal 20 November 2017. Populasi dalam penelitian ini yaitu keseluruhan siswa kelas X Kria Tekstil SMK Negeri 1 Berastagi yang terdiri dari 3 kelas berjumlah 92 siswa. Hasil penelitian ini menunjukan bahwa kemampuan menggambar ornamen suku batak karo motif pantil manggus pada media styrofoam siswa kelas X SMK Negeri 1 Berastagi baik. Hasil rata-rata hitung kemampuan siswa yaitu 89,5 standart deviasi 3,40 dengan nilai tertinggi 96 dan nilai terendah 83.Kata Kunci : Ornamen, Styrofoam